Więcej niewiadomych wytrzymać w dziejach myślenia. Dialogi Junga i Heideggera z Nietzschem - Kostyszak, Maria (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2007)
The article, being a part of the just prepared book, deals with two different interpretations of Nietzschean text. C. G. Jung devoted five years' Seminar to discuss "Thus spoke Zarathustra" in the Psychological Club (1934–39), M. Heidegger was giving lectures and developing his controversy (Auseinandersetzung) with Nietzsche between 1934–48, some pauses including. The thesis exposed in the article suggests that in Nietzsche's text they were looking for the kind of language, capable to generate transformation of individual and general culture of being. The quest for such a regenerative code is explored in three main semantic fields: the "natural", the sacred and the artistic. The task of regaining "natural" character of human unity, despite of theoretical inadequacy of the category of "nature"; the aim of taking care of alive essence of sacrum as well as the possibilities of regeneration that may be found in the sphere of artistic experience, are considered in the light of Jungian and Heideggerian perspectives of reading Nietzsche. Ambivalence of their interpretations helps to show also certain continuous difficulties to get access to the sources of life. To endure these, at first unknown, conditions of our lives, allows the mind to learn and shape thinking from experience. Jung's and Heidegger's dialogues with Nietzsche may let us see that enduring in the unknown does not have to paralyze the growth of thinking.